2022
DOI: 10.3762/bjnano.13.94
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of zinc oxide nanoparticles toward highly efficient photocatalysis and antibacterial application

Abstract: Zinc oxide nanoparticles (ZnO NPs) were successfully synthesized by a green method using rosin and zinc chloride as salt precursors. The phase structure, morphology, and particle size of ZnO were determined by X-ray powder diffraction, field emission scanning electron microscopy, and high-resolution transmission electron microscopy. The fabricated ZnO NP samples are crystalline with a grain size of 30–100 nm. The ZnO NPs were used as catalysts for the photodegradation of methylene blue (MB) and methyl orange (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The degradation of MB dyes occurs when the strong oxidizing component (HO • ) attacks them forming carbon dioxide and the water molecule as byproducts (Eq. 14) [33a,61–63] . As shown in the reactions, the O 2 • − and HO • are two leading reactive species for the photodegradation of the MB dyes.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The degradation of MB dyes occurs when the strong oxidizing component (HO • ) attacks them forming carbon dioxide and the water molecule as byproducts (Eq. 14) [33a,61–63] . As shown in the reactions, the O 2 • − and HO • are two leading reactive species for the photodegradation of the MB dyes.…”
Section: Resultsmentioning
confidence: 94%
“…14). [33a, [61][62][63] As shown in the reactions, the O 2 *À and HO * are two leading reactive species for the photodegradation of the MB dyes.…”
Section: Mechanism Of Mb Dye Degradationmentioning
confidence: 98%
“…The surface plasmon resonance (SPR) peak serves as a crucial indicator for determining nanoparticle size and uniformity. In this instance, the distinctness of the SPR peak suggests the formation of monodisperse ZnO NPs [65]. Typically, ZnO NPs display a maximum absorption peak wavelength within the 300-380 nm range.…”
Section: Characterization Of Zno Npsmentioning
confidence: 97%
“…[ 101 ] Rosin derived from Pinus latteri trees was reacted with the combination of zinc chloride and NaOH to produce zinc resinate initially, and then post‐calcination was performed to produce ZnO NPs. [ 102 ] The size of ZnO was recorded to be 30–100 nm, with an average size of about 60 nm, and it exhibited a band gap of 3.15 eV. The photocatalytic efficiency towards MB and methyl orange (MO) degradation was recorded to be 100% and 82.78%, respectively, under UV radiation for 210 min.…”
Section: Zinc Oxide Nanostructures Enabled Photo‐degradation Of Dyesmentioning
confidence: 99%
“…[ 105 ] Cannabis sativa leaf extract was used to prepare ZnO NPs and silver (Ag)‐doped ZnO NPs, which were then tested for dye degradation efficiency under visible irradiation for 80 min. [ 102 ] Results showed that the Ag‐doped ZnO NPs (96%) exhibited much improved degradation efficiency as compared to bare ZnO NPs (38%) towards Congo red (CR) dye. However, it was recorded to be 94% (Ag‐ZnO NPs) and 35% (ZnO NPs) for MO under the same experimental conditions.…”
Section: Zinc Oxide Nanostructures Enabled Photo‐degradation Of Dyesmentioning
confidence: 99%